Mechanical spring discharge-based multipillar triboelectric nanogenerator with enhanced power output. (March 2023) - Kim, Dongchang; Heo, Deokjae; Cha, Kyunghwan; Song, Myunghwan; Son, Jin-ho; Kim, Sunghan; Lin, Zong-Hong; Choi, Kyungwho; Chung, Jihoon; Lee, Sangmin
Abstract: With the extensive use of small portable electronics in digital healthcare, the triboelectric nanogenerator (TENG), which can convert mechanical energy into electricity, has been developed for these portable electronics. However, the high mechanical input power for TENG performance improvement causes constant damage and excessive noise, which can make applying portable devices in daily life inconvenient. Nevertheless, the TENG electrical limitation, generating a low current output as nanoampere to microampere, still is not overcome. In this study, a portable multipillar TENG (PMP-TENG) with conductive springs can provide amplified output, developed mechanical characteristics simultaneously. When a moving electrode with a surface charge contacts the springs, the PMP-TENG continuously generates a high discharge output and increases the output frequency through the elastic force of the spring. In addition, the spring can prevent crack damage and harmful noise via shock absorption of the moving electrode. During the PMP-TENG operating mechanical input of 2.5 Hz, the average peak voltage, current is 165 V, 34 mA, respectively. The PMP-TENG is used to charge small electronics or power warning lights in portable devices during human motion, such as walking, running, and jumping, increasing its advantages. Graphical Abstract: ga1 Highlights: Triboelectric nanogenerator(TENG) utilizing conductive spring for amplifying output. The conductive spring enhances current output by allowing electrons to flow directly. The conductive spring increases the mechanical lifespan by increasing the impact time.